Does COVID-19 Pandemic Impact on Financial Difficulties in Indonesian Tourism Sector Companies? - Widyaningsih Azizah; Hotman Fredy; Sri Irviati Wahyoeni; M. Izzah Al Islami; Putri Ayu Milani (PT Mattawang Mediatama Solution, 2023)
President of the Republic of Indonesia, Joko Widodo has determined the strategic role of tourism as a leading sector in national development in his two leadership periods. However, since the emergence of the Covid-19 outbreak in early 2020, the tourism industry and its related sectors, including hotels, food and beverage establishments, cleaning services, local tour guides, and transportation, have experienced considerable setbacks. The performance of the tourism industry amid the Covid-19 outbreak has received significant attention. The Covid-19 outbreak, which began in 2020, has restricted people’s mobility, particularly impacting the travel of international tourists to Indonesia. Companies operating in the tourism sector, such as those in the hotel, resort, and cruise line industries, now face various risks, such as decreasing revenue and operating income. This decline will undoubtedly result in financial hardships. This study examines the differences in financial distress and litigation risk of hotel, resort, and cruise line sub-industry companies prior to and following the onset of the pandemic. The Paired Sample T-test is utilized for hypothesis testing, contingent upon fulfilling the normality test requirement. However, if the normality test results indicate the non-normal distribution of residuals, non-parametric statistical methods, such as the McNemar test and Wilcoxon test, will be utilized for data analysis. The study presents findings that demonstrate differences in financial distress and litigation risk within the Hotel, Resort, and Cruise Line Sub-Industry companies prior to and following the pandemic.